Operative treatment for the painful posterior thigh after hamstring autograft harvesting - Laakso M.; Kosola J.; Niemi P.; Mäkelä K.; Ranne J.; Orava S.; Lempainen L. (CIC EDIZIONI INT, 2022)
Background: Semitendinosus (ST) is widely used autograft in anterior cruciate ligament reconstructions (ACLR). Although tendon harvesting is a common procedure, some patients exhibit pain, cramping and dysfunction in posterior thigh after the ACLR. The formation of the newly regenerated neotendon could be compromised by a new injury or too rapid rehabilitation. We present this clinical entity and the developed surgical technique and share our experience in treatment of these patients.Methods: Ten patients underwent operation where the harvested, retracted and loose muscle (9 ST, 1 gracilis) was reattached again. The delay to the diagnosis and the outcome of the procedure were recorded. Cases were followed and magnetic resonance images (MRI) were included from 2 cases for the demonstration of postoperative healing.Results: Six ST and the gracilis patients with prolonged symptoms had good results and returned to their normal activity level. Preoperative MRI showed increased signal intensity and edema of the harvested and retracted muscles as the sign of compromised healing of the neotendon. Post-operatively, these MRI findings were resolved.Conclusions: In high activity level patients with chronic posterior thigh pain and cramping of the harvested muscle, the stabilization procedure of the poorly healed muscle belly could lead to beneficial outcome.